2018
DOI: 10.1111/jam.13674
|View full text |Cite|
|
Sign up to set email alerts
|

Significant improvement of intestinal microbiota of gibel carp (Carassius auratus gibelio ) after traditional Chinese medicine feeding

Abstract: This study may provide useful information for further application of TCM for diseases prevention and stress management in aquaculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…indicated that the core intestinal microbiota of gibel carp was Proteobacteria and Firmicutes (Wu, Tian, et al, ; Wu, Ding, et al, ). Recent studies from several groups showed that Fusobacteria , Proteobacteria , Bacteroidetes , Cyanobacteria and Firmicutes were the dominant phyla in the gut of gibel carp (Li et al, ; She et al, ; Wu et al, ). In line with these studies, the most abundant phyla of gibel carp detected in the present study were Fusobacteria , Bacteroidetes and Proteobacteria in both control and fucoidan‐treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…indicated that the core intestinal microbiota of gibel carp was Proteobacteria and Firmicutes (Wu, Tian, et al, ; Wu, Ding, et al, ). Recent studies from several groups showed that Fusobacteria , Proteobacteria , Bacteroidetes , Cyanobacteria and Firmicutes were the dominant phyla in the gut of gibel carp (Li et al, ; She et al, ; Wu et al, ). In line with these studies, the most abundant phyla of gibel carp detected in the present study were Fusobacteria , Bacteroidetes and Proteobacteria in both control and fucoidan‐treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, the most dominant genus was Cetobacterium that is significantly increased in response to 30 g/kg fucoidan treatment . Cetobacterium belongs to phylum Fusobacteria and has been previously detected to be the dominant genus in the intestine of many fresh water fish flora including gibel carp (Li et al, ; Wu et al, ; Xia et al, ). Earlier studies reported that Cetobacterium is involved in fermentation of peptides and carbohydrates and synthesis of vitamin B 12 (Sugita, Miyajima, & Deguchi, ; Tsuchiya, Sakata, & Sugita, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…wiley.com/doi/10.1111/jam. 13674 In the paper by Wu et al (2018), the following errors were published on page 832 under the Results section:…”
mentioning
confidence: 99%
“…Manuscript to be reviewed innate immunity (Liu et al, 2017;Patterson et al, 2017). Potential probiotics including Bacillus, Acidobacteria, and Lactococcus (Bernardeau et al, 2017;Lv et al, 2016;Wu et al, 2018) were predominant in the midgut mucosa and Lactobacillus were predominant in the hindgut mucosa.…”
Section: Discussionmentioning
confidence: 99%